A brain tumor computer-aided diagnosis method with automatic lesion segmentation and ensemble decision strategy - Yu, Liheng; Yu, Zekuan; Sun, Linlin; Zhu, Li; Geng, Daoying (Frontiers in Medicine, 2023)
Objectives: Gliomas and Brain Metastases (Mets) are the most common brain malignancies, the treatment strategy and clinical prognosis of patients are different, requiring accurate diagnosis of tumor types. However, the traditional radiomics diagnostic pipeline requires manual annotation and lacks integrated methods for segmentation and classification. To improve the diagnosis process, a Gliomas and Mets computer-aided diagnosis method with automatic lesion segmentation and ensemble decision strategy on multi-center datasets was proposed.Methods: 1022 high-grade Gliomas and 775 Mets patients' preoperative MR images were adopted in the study, including contrast-enhanced T1-weighted (T1-CE) and T2-Fluid Attenuated Inversion Recovery (T2-flair) sequences from 3 hospitals. Two segmentation models trained on the gliomas and Mets datasets respectively were used to automatically segment tumors. Multiple radiomics features were extracted after automatic segmentation. Several machine learning classifiers were used This is a provisional file, not the final typeset article to measure the impact of feature selection methods. A weight soft voting (RSV) model and ensemble decision strategy (EDPK) was introduced in the radiomics pipeline. Accuracy, sensitivity, specificity, and the area under the receiver operating characteristic curve (AUC) were used to evaluate the classification performance.The proposed pipeline improved the diagnosis of gliomas and Mets with ACC reaching 0.8950 and AUC reaching 0.9585 after automatic lesion segmentation, which was higher than those of the traditional radiomics pipeline (ACC:0.8850, AUC:0.9450).The proposed model accurately classified gliomas and Mets patients using MRI radiomics. The novel pipeline showed great potential in diagnosing gliomas and Mets with high generalizability and interpretability.